Spectroscopic and Thermogravimetric Investigation of Cd(II) Dinonyldithiophosphate: Removal of Cadmium from Aqueous Solutions - Nermin Biricik; Hadice Budak Gümgüm; Bahattin Gümgüm (Journal of Chemistry)
Dinonyldithiophosphoric acid (HDDTP) was synthesised from the reaction of phosphorus pentasulphide and nonyl alcohol. Dinonyldithiophosphate complex of cadmium [Cd(DDTP)2] was prepared by mixing solutions of Cd(II) with HDDTP in ethanol at room temperature. The acid and its complex were characterised by elemental analysis and spectroscopy. The thermal behaviour of Cd(DNDTP)2 was investigated by thermogravimetric analysis. Removal of Cd(II) from aqueous media by HDDTP solution was also studied. The optimum conditions for removal of Cd(II) were investigated for effects of solvent, pH, contact time, concentration, and inorganic anions. Cd(II) was quantitatively removed from aqueous solutions at the pH range of 0.5<pH<6, under the conditions that the stoichiometric ratio of HDDTP/Cd(II) ≥2/1. It can be stated that contact of the Cd(II) with HDDTP was sufficient for quantitative removing of cadmium from acidic aqueous solutions.